Porous adsorbent
A porous adsorbent with a specific surface structure and material composition achieves a strong adsorption force, addressing the limitations of existing adsorbents in supporting heavier objects while maintaining smooth surface interaction.
Patent Information
- Application Number
- JP2021069149
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-15
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2041-04-15
AI Technical Summary
Existing adsorbent materials used for detachable attachment to objects lack sufficient adsorption force, limiting their application to light-weight members such as paper and film.
A porous adsorbent with an adsorption surface featuring countless micropores, an area ratio of openings between 10 to 40%, and a specific surface shape, including a continuous opening of 75 μm or more and a smoothing section with a low level difference, is developed. This adsorbent is made from a rubber material with a laminated structure and specific pore sizes in each layer.
The porous adsorbent achieves a strong adsorption force without leaving marks on the surface, allowing for effective attachment and detachment of moderate to heavier objects, while maintaining surface smoothness and adsorption efficiency.
Smart Images

Figure 0007667398000002 
Figure 0007667398000003 
Figure 0007667398000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous adsorbent having adsorptivity for an object. [Background technology]
[0002] Sheet-like adsorption members that can be attached and detached to objects without using adhesive materials such as adhesives are used in various applications. For example, as described in Patent Documents 1 to 3, porous sheet-like members that can be attached to objects by the suction cup effect of micropores formed on the surface are known. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-171054 A [Patent Document 2] JP 2002-363330 A [Patent Document 3] Japanese Patent Application Publication No. 04-45189
[0004] Patent Document 1 describes an adsorption laminate in which the surface of a foamed layer formed by foaming an acrylic resin is cut or removed to form a suction cup layer surface. Patent Document 2 describes an acrylic foam sheet obtained by pressurizing an emulsion containing an acrylic resin with gas, applying it to the surface of a sheet with low air permeability, and heating it, and has a structure in which the bubble diameter decreases from the sheet surface side to the adsorption surface side. Patent Document 3 describes a resin microporous film in which the surface layer of the part where no micropores are formed is a smooth part with an unevenness of 6 μm or less.
[0005] Adsorption members that can be attached and detached to objects without using an adhesive member have the advantage of not leaving any adhesive marks or scratches on the adsorption surface, and therefore have a wide range of applications. The adsorption members described in Patent Documents 1 to 3 have the above advantages, but on the other hand, their adhesive power is not necessarily strong, and they are mainly used for posters, stickers, and anti-slip carpets, and are only capable of supporting relatively lightweight materials such as paper and film. Summary of the Invention [Problem to be solved by the invention]
[0006] The inventors of the present invention have made extensive research into this problem and have attempted to solve it. The problem that the present invention aims to solve is to provide an adhesive body that can be detachably attached to an object and has a strong adhesive force, and a manufacturing method thereof. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides an adsorption surface having a countless number of micropores. It can be attached to objects by the suction cup effect. A porous adsorbent comprising: The micropores are dissolution holes for a soluble powder, The porous adsorbent is characterized in that the area ratio of the openings in the adsorption surface is 10 to 40%.
[0008] Furthermore, the suction surface has a continuous opening portion having a major axis of 75 μm or more formed by portions of the opening portions being connected to each other, and a smooth portion that does not include the continuous opening portion, and it is preferable that the level difference Sk of the core portion measured in accordance with ISO25178 using the smooth portion as a measurement area is 8.5 μm or less, and it is even more preferable that Sk is 3.0 μm or less.
[0009] The smooth portion has an average area of 110 μm per recess deeper than the lower limit of the core portion. 2 It is preferable that:
[0010] In addition, the porous body is preferably made of a rubber material.
[0011] It is also preferable that two or more types of porous bodies are laminated.
[0012] It is also preferable that the rubber composition comprises a first layer having the smooth portion and a second layer vulcanization-bonded to the first layer, the first layer having a smaller pore size than the second layer, and the pores of each layer being interconnected.
[0014] In addition, it is preferable that the hardness of the first layer, measured with a C-type hardness scale, is at least 15 higher than that of the second layer.
[0015] It is also preferable that the pore size of the first layer is 5 to 100 μm, and the pore size of the second layer is 100 to 300 μm.
[0016] The method for producing a porous adsorbent is characterized in that a soluble powder that can be dissolved and removed with water or other solvent is kneaded with unvulcanized rubber or resin to form a master batch, the master batch is formed into a sheet, heated and pressurized, and then the soluble powder is washed and removed.
[0017] Also, a preferred method for producing a porous adsorbent is characterized in that the first masterbatch and a second masterbatch obtained by kneading a soluble powder having a larger particle size than the soluble powder used in the first masterbatch are each formed into sheets and laminated, and then the soluble powder is washed and removed.
[0018] The raw material of the master batch is preferably unvulcanized rubber. Effect of the Invention
[0019] The present invention makes it possible to provide an adhesive body that can be detachably attached to an object and has a strong adhesive force. [Brief description of the drawings]
[0020] [Figure 1] 1 is a schematic diagram showing a cross section of a porous adsorbent according to a first embodiment. [Diagram 2]FIG. 2 is a schematic diagram showing the adsorption surface of a porous adsorbent. [Diagram 3] FIG. 4 is a schematic diagram showing a cross section of a porous adsorbent according to a second embodiment. [Figure 4] 1 is an electron microscope photograph (magnification: 500 times) showing a cross section of a porous adsorbent according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] (First embodiment) The following describes the embodiments of the invention. As shown in Fig. 1, the porous adsorbent 1 of the first embodiment has an adsorption surface 22 on which a countless number of small diameter pores 23 are formed, and is a porous body that can be adsorbed in a freely attachable and detachable manner to an adhesion surface 9, which is a smooth surface of an object to be adhered.
[0022] (Adsorption principle) The principle by which the porous adsorbent 1 adheres to the smooth surface 9 to be adhered will be described. As described above, the adsorption surface 22 of the porous adsorbent 1 has numerous small holes 23, which are minute holes. When the porous adsorbent 1 is pressed from the opposite side of the adsorption surface 22 and pressed against the surface 9 to be adhered, the small holes 23 are crushed and adhere to the surface 9 to be adhered, and the air in the small holes 23 is released. When the pressure is released and the small holes 23 return to their original shape, the space in the small holes 23 becomes negative pressure and acts as a suction cup, so that the porous adsorbent 1 can be adsorbed to the surface 9 to be adhered. In addition, the adsorbed porous adsorbent 1 can be peeled off without leaving any trace on the smooth surface. These are the same adsorption principles as known micro suction cups.
[0023] As a result of extensive investigations into obtaining a porous adsorbent 1 with strong adsorption power, the inventors have found that the area ratio of the openings 231 formed by the small diameter holes 23 in the adsorption surface 22 is related to the strength of the adsorption power of the porous adsorbent 1. In the embodiment, when calculating the area ratio of the openings 231 in the adsorption surface 22, the openings 231 are defined as valleys deeper than the lower limit level of the core portion measured in accordance with ISO25178.
[0024] (Regarding the level difference Sk between the core and core parts) In the embodiment of the present invention, the core portion and the level difference Sk between the core portions are terms defined in the international standard for three-dimensional surface texture (ISO 25178). These terms will now be described.
[0025] In the present invention, the level difference Sk of the core part, which is one of the functional parameters defined in ISO25178, an international standard that specifies a method for evaluating the surface roughness of an object, is used as a parameter representing the surface shape of the porous adsorbent. The method for measuring the level difference Sk of the core part is to first obtain a reference surface (a plane of average height) of a measurement area (M pixels vertically and N pixels horizontally) on the surface of the object to be measured, and measure the variation in height when the height of the reference surface is set to 0. If the measured height data is expressed as a cumulative frequency distribution in descending order, a curve is obtained in which the vertical axis is the height and the horizontal axis is the ratio of the area of the actual part at that height. This curve is the load curve, and the ratio of the area of the area above a certain height c is the load area ratio at height c.
[0026] The position where the slope of the secant line of the load curve where the difference in areal load ratio is 40% is the minimum is called the center of the load curve, and the straight line where the sum of the squares of the deviation in the vertical axis direction from this center is the minimum is called the equivalent line. The surface obtained by removing from the measurement area the area that is not included in the height range of the equivalent line between 0% and 100% areal load ratio is called the core part, and the value obtained by subtracting the minimum height from the maximum height of the core part is called the level difference Sk of the core part. It can be said that the smaller the value of the level difference Sk of the core part, the higher the smoothness.
[0027] In the adsorption surface 22 of the porous adsorbent 1 according to the embodiment of the present invention, the area ratio of the openings 231, which are valleys deeper than the lower limit level (minimum height) of the core, is 10 to 40%. It has been found by the inventors' experiments that the porous adsorbent 1 has strong adsorption performance when the openings 231 are formed with such an area ratio. It is presumed that if the area ratio of the openings 231 is smaller than this, the area of the part that creates a negative pressure state is reduced and the suction cup effect is reduced, and if the area ratio is larger than this, the area of the part that adheres to the adherend surface 9 is reduced and the adsorption force is reduced. In this way, in the present invention, the countless small diameter holes 23 form the openings 231 on the adsorption surface 22 to play the role of micro suction cups, and since the openings 231 exist with an area ratio of 10 to 40%, it is possible to obtain a porous adsorbent 1 that has strong adsorption force for a smooth adherend surface 9 without using an adhesive or cohesive member. It is more preferable that the area ratio of the openings 231 is 15 to 30%.
[0028] (Surface shape of smooth portion 221) 2, the adsorption surface 22 has continuous openings 222 with a major axis of 75 μm or more formed by connecting parts of the small diameter holes 23, and a smooth portion 221 that does not include the continuous openings 222. In order to improve the adsorption force, it is preferable to increase the surface smoothness of the smooth portion 221.
[0029] In the present invention, the level difference Sk of the core portion described above is used as a parameter representing the surface shape (smoothness) of the smooth portion 221. When the smooth portion 221 is measured as a measurement area, the smaller the value of the level difference Sk of the core portion, the higher the smoothness of the smooth portion 221. When the smoothness of the smooth portion 221 is high, the adsorption surface 22 and the adherend surface 9 are closely attached to each other, and air that inhibits adsorption between the two is less likely to enter, improving the adsorption performance of the porous adsorbent 1. Experiments by the inventors have revealed that the level difference Sk of the core portion of the smooth portion 221 is preferably 8.5 μm or less, and more preferably 3.0 μm or less.
[0030] In addition to the smooth surface, the smooth portion 221 preferably has small recesses formed by micropores and is evenly distributed. Specifically, in the smooth portion 221, the average area of each recess deeper than the lower limit level of the core portion (the boundary between the core portion and the protruding valley portion defined in ISO25178) is 110 μm 2 In this embodiment, a laser microscope (Nanosearch SFT-4500, manufactured by Shimadzu Corporation) was used to measure the smooth portion 221 at a measurement visual field of 500 times, the number and area of the recesses present in the measurement region were measured, and the average area per recess was calculated therefrom.
[0031] It can be said that the smaller the average area per recess, the smaller and more uniformly the recesses formed by micropores are distributed in the smooth portion 221. This results in a uniform distribution of the points in the suction cup mechanism that are in a negative pressure state, without bias, and improves the adhesion between the suction surface 22 and the adherend surface 9.
[0032] (Suitable material) Moreover, the porous adsorbent 1 is preferably made of a rubber material that has a strong restoring force after being compressed and deformed. By using a rubber material, the elasticity of the porous adsorbent 1 is improved, and the effect of the micro-suction cup is enhanced, resulting in strong adsorption performance.
[0033] Second embodiment The porous adsorbent 1 may have a laminated structure including two or more kinds of porous bodies. In the second embodiment shown in Fig. 3 and Fig. 4, the porous adsorbent 1 is formed by laminating two layers of porous bodies made of a rubber material and integrating them, and includes a first layer 21 having an adsorption surface 22 capable of adsorbing to the adherend surface 9, and a second layer 31 vulcanization-bonded to the first layer 21 on the opposite side of the adsorption surface 22. The first layer 21 has small diameter holes 23, which are minute holes, and the second layer 31 has large diameter holes 33, which are larger in diameter than the small diameter holes 23. A part of the small diameter holes 23 is exposed and open on the adsorption surface 22, and the small diameter holes 23 can be adsorbed detachably to the smooth adherend surface 9 by the suction cup effect. In addition to the adsorption surface 22, a part of the small diameter holes 23 or the large diameter holes 33 is exposed on the surfaces of the first layer 21 and the second layer 31, and is open on each surface.
[0034] The small diameter holes 23 are in communication with each other, and the large diameter holes 33 are in communication with each other. In addition, since the first layer 21 and the second layer 31 are vulcanization bonded, there is no adhesive layer or the like at the boundary surface 4, which is the boundary between the first layer 21 and the second layer 31, and communication between the small diameter holes 23 and the large diameter holes 33 is not inhibited. Therefore, a communication structure is formed between the small diameter holes 23 and the large diameter holes 33 across the boundary surface 4.
[0035] The porous adsorbent 1, which is made of a rubber material, is flexible, and when pressed against the surface 9 to be adhered, the second layer 31 is significantly deformed so as to be recessed. Accordingly, the large holes 33 inside the second layer 31 are also deformed and crushed. When the pressure is subsequently released, the elastic restoring force of the rubber material causes the large holes 33 to return to their original shape. Since the large holes 33 and the small holes 23 are in communication, when the crushed large holes 33 expand again, the air contained inside the first layer 21 is sucked up toward the second layer 31, and the numerous small holes 23 are placed in a negative pressure state, allowing the porous adsorbent 1 to be strongly adhered to the surface 9 to be adhered.
[0036] (Difference in hardness between the two layers) In addition, the second layer 31, which has a larger pore size, is softer than the first layer 21. Therefore, when the above-mentioned pressing force is applied, mainly only the second layer 31 deforms, and the pressing force is dispersed. This prevents the pressing force from concentrating on a small area, and the adsorption surface 22 is pressed against the adherend surface 9 over a wide area. By pressing the wide area of the adsorption surface 22 against the adherend surface 9 evenly, the deformation of the adsorption surface 22 when pressed is suppressed, and the adhesion between the adsorption surface 22 and the adherend surface 9 is improved, and air pockets are less likely to form between the two, resulting in a strong adsorption effect.
[0037] The hardness of each layer can be set appropriately, but since it is desirable for the adsorption surface 22 to adhere closely to the adherend surface 9, it is preferable that the first layer 21 has a hardness that does not deform too much when pressed from the pressing surface 32 side. On the other hand, it is preferable that the second layer 31 is formed softly. If the second layer 31 is formed softly, only the second layer 31 can be largely deformed when pressed, and not only can the effect of increasing the adhesion between the adsorption surface 22 and the adherend surface 9 be obtained, but the large diameter holes 33 are largely crushed as the second layer 31 is compressed, and air can be sucked up more strongly when the shape is restored. In the embodiment, the first layer 21 has a hardness of 45° and the second layer 31 has a hardness of 15°. Thus, it is preferable that the hardness difference between the two layers is 15 or more higher than that of the second layer when measured with a C-type hardness meter. If the hardness difference is less than 15, the effect brought about by the hardness difference between the two layers as described above is reduced, and the adsorption force is reduced.
[0038] (About dissolution holes in soluble powders) In addition, the micropores formed in the porous adsorbent 1 are preferably elution holes of a soluble powder. As described in detail later, the small diameter holes 23 and the large diameter holes 33 of the porous adsorbent 1 of the embodiment are obtained by kneading a soluble powder that can be dissolved and removed by water or other solvents with unvulcanized rubber, forming a master batch into a sheet, vulcanizing the sheet, and then washing and removing the soluble powder. In the embodiment, salt is used as the soluble powder. By forming two master batches of kneaded salts with different particle sizes into a sheet and vulcanizing and bonding them, a two-layer structure porous adsorbent 1 having a layer with a large pore size and a layer with a small pore size can be obtained. In addition, since the micropores are salt elution holes, the micropores can be made into homogeneous continuous pores.
[0039] When pores are formed by mechanical foaming or chemical foaming as described in Patent Documents 1 to 3, the structure of the resulting porous body depends on the behavior of the gas that forms the pores, so it is not easy to control the pore size, porosity, and pore distribution. If the small diameter pores 23 and the large diameter pores 33 are elution holes of a soluble powder as in the embodiment of the present invention, it is easy to make the pore size of each layer uniform or to form fine pores by manipulating the particle size of the soluble powder. In addition, if the soluble powder is polygonal, the elution holes will also be polygonal, and micro-connections between the pores will be easily formed, further increasing the adsorption force.
[0040] (Regarding pore size) It is also preferable that the pore size of the first layer 21 is 5 to 100 μm, and that of the second layer 31 is 100 to 300 μm. If the pore size is larger than this range, the hardness of the porous adsorbent 1 decreases and the porous adsorbent 1 becomes soft, so that when a load is applied parallel to the adsorbing surface 22, a part of the porous adsorbent 1 may deform and peel off.
[0041] (raw materials) The raw materials for producing the porous adsorbent 1 of the present invention will be described. At least unvulcanized rubber, soluble powder, and vulcanizing agent are used as the raw materials for the porous adsorbent 1. Examples of rubber that can be used include natural rubber or synthetic rubber with a molecular weight of about 10,000 to 100,000 (JIS K6300 Mooney viscosity = about 70 to 95). Examples of synthetic rubber that can be used include butadiene-styrene copolymer, butadiene-acrylonitrile copolymer, chloroprene, polyurethane rubber, etc. In particular, butadiene-acrylonitrile copolymer (nitrile content 31 to 42%) is excellent in oil resistance, aging resistance, elasticity, and toughness, and is therefore optimal as a porous adsorbent. It should be noted that a porous adsorbent can also be obtained by foaming or sintering resins such as urethane and polyethylene instead of rubber materials, but it is preferable to use rubber materials because they have poor adsorption power.
[0042] Examples of soluble fine powders that can be used as raw materials include fine powders of salt, sugar, etc. Salt refers to an inorganic compound that is easily pulverized, does not decompose and gasify at the rubber curing temperature (110°C to 160°C), and can be easily removed with water after heating. Specifically, salts such as sodium chloride, sodium sulfate, and sodium nitrate are used. As for sugar, any of monosaccharides such as pentose and hexose, disaccharides such as saccharose and maltose, and polysaccharides such as starch and glycogen can be used, and further, these can be used in combination.
[0043] Examples of vulcanizing agents that can be used include known vulcanizing agents such as sulfur, selenium, tellurium, sulfur chloride, etc. In addition, additives such as fillers, curing assistants, and curing accelerators can also be used as necessary.
[0044] (Method for manufacturing the porous adsorbent 1 of the first embodiment) A method for manufacturing the porous adsorbent 1 of the first embodiment will be described. In this embodiment, a dissolution method is used in which raw materials are mixed with a soluble powder such as sodium chloride, vulcanized, and then the soluble powder is dissolved to form a porous body. Specifically, the above-mentioned various raw materials (unvulcanized rubber, soluble fine powder, vulcanizing agent) are put into a kneader and kneaded to form a master batch.
[0045] Next, the master batch is placed in a mold as a flat sheet, vulcanized, heated and pressurized, and released from the mold after vulcanization. The water-soluble fine powder is washed out while repeatedly compressing and expanding and restoring the material using cold or hot water, to obtain the porous adsorbent 1.
[0046] (Method for manufacturing the porous adsorbent 1 of the second embodiment) Next, a method for producing the porous adsorbent 1 according to the second embodiment will be described. In the second embodiment, a first master batch is prepared by kneading a soluble powder having a small particle size, and a second master batch is prepared by kneading a soluble powder having a large particle size. The diameter of the soluble powder kneaded in the first master batch is preferably 5 to 100 μm, and the diameter of the soluble powder kneaded in the second master batch is preferably 100 to 300 μm.
[0047] Next, each master batch is made into a flat sheet, the sheets are stacked and placed in a mold, and heated and pressurized to vulcanize and bond the two layers. After vulcanization, the mold is released, and the water-soluble fine powder is washed out while repeatedly compressing and expanding and restoring the mixture using cold or hot water, to obtain a porous adsorbent 1 having a two-layer structure.
[0048] As described above, by producing the porous adsorbent 1 by the elution method, it is possible to ensure the interconnection of the large diameter pores 33 and / or the small diameter pores 23, and also to obtain a porous adsorbent 1 with good surface smoothness. The smaller the surface roughness of the smooth portion 221 of the adsorbing surface 22, the tighter the adhesion between the adsorbing surface 22 and the adherend surface 9 becomes, making it difficult for air to exist between them, resulting in a state close to a vacuum and increasing the adsorption strength.
[0049] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. For the examples and comparative examples, the area ratio of the openings, the level difference Sk between the core parts of the smooth part and the average area per recess formed by the micropores in the smooth part, the hardness measured by a C-type hardness tester, the average value of the pore diameter and the pore continuity, the total thickness of the sample, and the evaluation results of the adsorption properties of the porous body are as shown in Table 1.
[0050] Example 1 100 parts of raw material NBR, 3.5 parts of sulfur, 5 parts of zinc oxide, 30 parts of softener, 50 parts of carbon black, 2 parts of antioxidant, and 700 parts of sodium chloride fine powder with a particle size of 44 to 74 μm were kneaded to form a master batch, which was then placed in a smooth mold as a flat sheet, and then pressed between hot platens with a pressure of about 20 MPa, and vulcanized for 60 minutes at a temperature of 120 ° C. After vulcanization, the mold was released, thoroughly washed with water until the sodium chloride fine powder was completely removed, and dehydrated and dried to obtain a porous body, which was designated as Example 1.
[0051] Example 2 Example 2 was prepared by preparing a porous body in the same manner as in Example 1, except that the amount of sodium chloride fine powder having a particle size of 140 to 300 μm was changed to 1200 parts.
[0052] Example 3 100 parts of raw material NBR, 3.5 parts of sulfur, 5 parts of zinc oxide, 30 parts of softener, 50 parts of carbon black, 2 parts of antioxidant, and 700 parts of sodium chloride fine powder having a particle size of 44 to 74 μm were kneaded to obtain master batch A, which was made into a flat sheet A having a thickness of 0.5 mm. Separately, 100 parts of raw material NBR, 3.5 parts of sulfur, 5 parts of zinc oxide, 30 parts of softener, 50 parts of carbon black, 2 parts of antioxidant, and 1200 parts of sodium chloride fine powder having a particle size of 140 to 300 μm were added and kneaded to obtain master batch B, which was made into a flat sheet B having a thickness of 4.5 mm. Next, the sheet A and the sheet B were overlapped and placed in a smooth mold, and then the sheet was pressed between hot platens by applying a pressure of about 20 MPa, and vulcanized at a temperature of 120 ° C for 60 minutes. After vulcanization, the mold was released, thoroughly washed with water until sodium chloride was completely removed, and then dehydrated and dried to obtain a porous body in which Sheet A and Sheet B were integrated, which was designated Example 3.
[0053] Example 4 A porous body was prepared as Example 4 in the same manner as in Example 3, except that the amount of the sodium chloride fine powder in Sheet B was changed to 900 parts.
[0054] Example 5 A porous body was prepared as Example 5 in the same manner as in Example 3, except that the amount of the sodium chloride fine powder in Sheet B was changed to 800 parts.
[0055] Comparative Example 1 The surface of the porous body of Example 2 was cut away and the skin layer was removed to prepare a porous body having an adsorption surface as Comparative Example 1.
[0056] Comparative Example 2 A master batch was prepared by kneading 100 parts of an olefin resin (manufactured by Mitsui Chemicals, Inc.; product name: TAFMER A4090S), 100 parts of polyethylene glycol (PEG), and 600 parts of sodium chloride fine powder having a particle size of 44 to 74 μm. The master batch was then extruded into a flat sheet, which was thoroughly washed with water until the sodium chloride fine powder was completely removed, and then dehydrated and dried to obtain a porous body, which was designated as Comparative Example 2.
[0057] (Area ratio of openings) The adsorption surface of the example was used as the measurement area, and the surface shape was measured using a laser microscope (Nano Search SFT-4500, manufactured by Shimadzu Corporation) in accordance with ISO 25178. The valleys deeper than the lower limit level of the measured core portion were regarded as openings, and the area ratio of the openings was calculated.
[0058] (Surface shape of smooth part) In the adsorption surface of the embodiment, the portion not including continuous openings having a major axis of 75 μm or more formed by connecting parts of the openings was set as the smooth portion, and the smooth portion was set as the measurement region, and the level difference Sk of the core portion was measured using a laser microscope (Nano Search SFT-4500, manufactured by Shimadzu Corporation) in accordance with ISO 25178. Note that the level difference Sk of the core portion was also measured in the same manner for the comparative example, but since the ratio of the openings in the comparative example was large and continuous openings were present in the viewing angle of the measurement region, the measured level difference Sk of the core portion was used as a reference value.
[0059] In addition, in the smooth portion of the example, the number and area of recesses deeper than the lower limit level of the core portion were measured when the smooth portion was used as the measurement area, and the average area per recess was calculated from the number and area.
[0060] (Calculation of average pore size and evaluation of pore continuity) The surfaces (adsorption surfaces) and cross sections of the porous bodies of the examples and comparative examples were observed using an electron microscope (manufactured by JEOL Ltd., magnification 50x), the average pore diameter was calculated, and the continuity of the pores was evaluated.
[0061] (Evaluation of ease of adsorption) The porous bodies obtained in the examples and comparative examples were each cut to a size of 120 mm x 150 mm to prepare samples, which were then pressed by hand against a glass surface with a smooth surface and parallel to the direction of gravity, with the 120 mm side oriented perpendicular to the surface, and the ease of adhesion was evaluated according to the following criteria. ⊚: The sample could be applied simply by pressing with one hand (the sample could be applied without applying a uniform load to the entire sample). ◯: The sample could be applied by pressing evenly with both hands (the sample could be applied by applying an even load to the entire sample). ×: Unable to attach.
[0062] (Evaluation of adsorption under constant load) The porous bodies obtained in the Examples and Comparative Examples were each cut to 120 mm x 150 mm and attached to a smooth glass surface parallel to the direction of gravity. A hook-shaped attachment was then fixed to each sample with adhesive tape, and a string with a weight (2 kg) was hung on the attachment. The condition after 24 hours was observed and evaluated according to the following criteria. ⊚: The sample remained attached to the glass surface. ○: It remained attached to the glass surface for about an hour. ×: Did not stick to glass surface.
[0063] (result) In all the examples and comparative examples, the continuity of the micropores was confirmed. This is thought to be because all the examples were created by the dissolution method. If the pores were open rather than closed, the air remaining between the adsorption surface and the adherend surface could escape, which would contribute to improving the adsorption properties.
[0064] It was confirmed that the porous bodies of Examples 1 to 5 all had good ease of adsorption to a glass surface and good adsorption properties under a constant load. In addition, when comparing Example 1 and Example 2, which have a single-layer structure, it was confirmed that Example 2, which has a smaller level difference Sk of the core part in the smooth part and a smaller average area per recess, was superior in ease of adsorption. With regard to adsorption properties under a constant load, Example 1, which has a higher hardness, was superior.
[0065] Furthermore, when comparing Examples 3 to 5 having a laminated structure of two layers with different hardness, Examples 3 and 4, in which the hardness of the first layer having an adsorption surface is 15 or more higher than that of the second layer, showed superior ease of adsorption. It was confirmed that Examples 3 and 4 showed good adsorption properties in both ease of adsorption and adsorption properties under a constant load.
[0066] On the other hand, in the comparative examples, it was confirmed that all of them had open cells, but did not have adhesive properties to the glass surface. In comparative example 1, the adhesive surface became rough due to the peeling off of the skin layer, and the area ratio of the openings became 78%, which is thought to have caused the adhesive power to be lost. In addition, in comparative example 2, in addition to the high area ratio of the openings, the surface smoothness was low, so air that inhibited adhesion entered, which is thought to have reduced the adhesive power. [Table 1] [Explanation of symbols]
[0067] 1. Porous adsorbent 21 First Layer 22 Adsorption surface 221 Smooth section 222 Continuous opening 23 Small diameter hole 231 Opening 31 Second Layer 32 Pressing surface 33 Large diameter hole 4. Boundary 9 Adhering surface
Claims
1. A porous adsorbent that can be adsorbed to an object by the suction effect of an adsorption surface formed with countless micropores, The micropores are dissolution holes for a soluble powder, A porous adsorbent, characterized in that the area ratio of openings in the adsorption surface is 10 to 40%.
2. the adsorption surface has continuous openings having a major axis of 75 μm or more formed by parts of the openings being connected to each other, and a smooth portion that does not include the continuous openings, 2. The porous adsorbent according to claim 1, wherein the smooth portion has a level difference Sk of 8.5 μm or less with respect to a core portion measured in accordance with ISO 25178 using the smooth portion as a measurement area.
3. 3. The porous adsorbent according to claim 2, wherein the smooth portion has a level difference Sk of 3.0 μm or less with respect to a core portion measured in accordance with ISO 25178 using the smooth portion as a measurement area.
4. The smooth portion has an average area of 110 μm per recess deeper than the lower limit of the core portion. 2 4. The porous adsorbent according to claim 2, wherein:
5. 5. The porous adsorbent according to claim 1, which is made of a rubber material.
6. 6. The porous adsorbent according to claim 1, wherein two or more types of porous bodies are laminated.
7. The porous adsorbent described in claim 6, characterized in that it comprises a first layer having the adsorbent surface and a second layer vulcanization-bonded to the first layer, the first layer having a smaller pore size than the second layer, and the pores of each layer being interconnected.
8. 8. The porous adsorbent according to claim 7, wherein the hardness of the first layer, measured with a C-type hardness tester, is at least 15 degrees higher than that of the second layer.
9. 9. The porous adsorbent according to claim 7, wherein the first layer has a pore size of 5 to 100 μm, and the second layer has a pore size of 100 to 300 μm.
10. A method for producing a porous adsorbent as described in any one of claims 1 to 5, characterized in that a soluble powder that can be dissolved and removed with water or other solvent is kneaded with unvulcanized rubber or resin to form a master batch, the master batch is formed into a sheet, heated and pressurized, and then the soluble powder is washed and removed.
11. A method for producing a porous adsorbent as described in any one of claims 6 to 9, characterized in that a first masterbatch and a second masterbatch kneaded with a soluble powder having a larger particle size than the soluble powder used in the first masterbatch are each formed into sheets and laminated, and then the soluble powder is washed and removed.
12. 12. The method for producing a porous adsorbent according to claim 10 or 11, wherein the raw material of the master batch is unvulcanized rubber.
Citation Information
Patent Citations
Finely porous membrane having excellent fixing property and its production
JP1992045189A
Suction laminated body
JP2001171054A
Acrylic foam sheet and manufacturing method therefor
JP2002363330A
Graphic sheet and building structure
JP2017218561A